Ethanolic Extract of Vitis thunbergii Exhibits Lipid Lowering Properties via Modulation of the AMPK-ACC Pathway in Hypercholesterolemic Rabbits. (28th March 2012) - Pan, Chun-Hsu; Tsai, Chia-Hua; Lin, Wen-Hsin; Chen, Guo-Yan; Wu, Chieh-Hsi
Abstract : Vitis thunbergii (VT) is a wild grape that has been shown to provide various cardioprotective effects. The present study was designed to examine whether a VT extract could reduce serum lipid levels and prevent atherogenesis in a hypercholesterolemic rabbit model. At the end of an 8-week study, our results showed that a VT extract supplement markedly suppressed the serum levels of cholesterol and low-density lipoprotein, reduced lipid accumulation in liver tissues, and limited aortic fatty streaks. Our findings suggest that the VT extract activated AMPK (5 ′ -adenosine monophosphate-activated protein kinase) with subsequent inhibition of the activation of ACC (acetyl-CoA carboxylase). Our results suggest that this VT extract could be further developed as a potential lipid-lowering agent and as a natural health food to prevent atherogenesis.